Comparison of cryogenic (hydrogen) and TESPEL (polystyrene) pellet particle deposition in a magnetically confined plasma. (5th January 2018) - McCarthy, K. J.; Tamura, N.; Combs, S. K.; Panadero, N.; Ascabíbar, E.; Estrada, T.; García, R.; Hernández Sánchez, J.; López Fraguas, A.; Navarro, M.; Pastor, I.; Soleto, A.
Abstract: A cryogenic pellet injector (PI) and tracer encapsulated solid pellet (TESPEL) injector system has been operated in combination on the stellarator TJ-II. This unique arrangement has been created by piggy-backing a TESPEL injector onto the backend of a pipe-gun–type PI. The combined injector provides a powerful new tool for comparing ablation and penetration of polystyrene TESPEL pellets and solid hydrogen pellets, as well as for contrasting subsequent pellet particle deposition and plasma perturbation under analogous plasma conditions. For instance, a significantly larger increase in plasma line-averaged electron density, and electron content, is observed after a TESPEL pellet injection compared with an equivalent cryogenic pellet injection. Moreover, for these injections from the low-magnetic-field side of the plasma cross-section, TESPEL pellets deposit electrons deeper into the plasma core than cryogenic pellets. Finally, the physics behind these observations and possible implications for pellet injection studies are discussed.